SEROLOGICAL AND MOLECULAR INVESTIGATION OF ZOONOTIC POTENTIAL OF HEPATITIS E VIRUS AMONG FARM ANIMALS IN TURKIYE - Caglar OKULMUS; Abdurrahman Anil CAGIRGAN; Yakup YILDIRIM; Ozge Sevinc KORKMAZ AKAR; Ali KUCUK (Journal of Animal and Plant Sciences, 2025)
The Orthohepevirus A strain of hepatitis E virus (HEV) is one of the world's leading zoonotic viruses and poses significant public health concerns. HEV susceptibility has been demonstrated in a wide range of animal species and have the capacity to transmit the virus to humans. However, the contribution of Orthohepevirus A serotypes to HEV epidemiology remains poorly understood. Blood serum samples were collected from 188 domestic animals from different farms selected by random sampling in Burdur province of Türkiye. The animal group consisted of 22 horses, 22 donkeys, 30 sheep, 25 goats, 27 cattle, 35 cats and 27 dogs. An overall HEV seroprevalence of 4.79% was observed. The presence of HEV antibodies in goats, horses, and donkeys was detected for the first time in Türkiye. Statistical tests performed to determine the difference between seropositivity rates according to animal species were found significant at p ≤ 0.05. Orthohepevirus A RNA was undetectable in all samples using gel-based nested RT-PCR. In this first report on HEV in farm animals in Türkiye, the presence of HEV antibodies suggests that farm animals may have an important role in spreading infection.
Keywords: Domestic animals; Hepatitis E virus; HEV antibodies; Türkiye; Zoonotic potential